Selected Decisions and Selected Documents of the International Monetary Fund, 38th Issue. (Selected Decisions; Thirty-Eighth Issue, 2016, 2016)
This volume documents decisions, interpretations, and resolutions of the Executive Board and Board of Governors of the International Monetary Fund, as well as documents relating to the United Nations and other international organizations.